Parents’ Perceptions on the Efficacy of Yorùbá Folktales in Cultivating Moral Values among the Youths - Badru, Surajudeen Adewale; Odutayo, Adesegun Olayide (Universitas Islam Negeri Walisongo Semarang, 2023)
A quantitative study of parents’ perception of the efficacy of Yoruba folktales in cultivating moral values among the youths in Oyo State of Nigeria was reported in this study. Six hundred twelve parents selected through accidental sampling technique participated in the study. A 14-item close-ended researcher-designed questionnaire was employed for data collection. Mean, standard deviation, and the t-test were used for data analysis. The study’s findings revealed that the parents’ perception of the efficacy of Yoruba folktales in cultivating moral values among the youths was high, and there was a significant gender influence on their perception. The study concluded that Yoruba folktales cultivate moral values among the youth. It was recommended that parents should intensify efforts in ensuring that they engage their children with folktale narration and employ the moral values embedded in the tales to mold and educate their children to become good citizens.